2012
DOI: 10.1136/annrheumdis-2012-201669
|View full text |Cite
|
Sign up to set email alerts
|

The risk of pulmonary embolism and deep vein thrombosis in rheumatoid arthritis: a UK population-based outpatient cohort study

Abstract: This population-based study indicates an increased risk of PE and DVT in RA, supporting increased monitoring of venous-thromboembolic complications and risk factors in RA, regardless of hospitalisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
87
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 45 publications
12
87
0
4
Order By: Relevance
“…Previous studies have demonstrated an increased risk of deep vein thrombosis and pulmonary embolism in patients with RA relative to the age and sex-matched general population without RA, likely due to the effects of systemic inflammation and endothelial dysfunction (50,51). Our findings may be the result of selection bias; it may be that healthier patients with RA are selected for THA and/or there may be an overall higher risk of venous thromboembolism among patients with advanced OA relative to the age and sex-matched general population without OA (52).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated an increased risk of deep vein thrombosis and pulmonary embolism in patients with RA relative to the age and sex-matched general population without RA, likely due to the effects of systemic inflammation and endothelial dysfunction (50,51). Our findings may be the result of selection bias; it may be that healthier patients with RA are selected for THA and/or there may be an overall higher risk of venous thromboembolism among patients with advanced OA relative to the age and sex-matched general population without OA (52).…”
Section: Discussionmentioning
confidence: 98%
“…Together, deep venous thrombosis and pulmonary embolism constitute venous thromboembolism, the risk of which is increased in patients with rheumatoid arthritis and other autoimmune disorders (2)(3)(4)(5)(6)(7). A possible mechanism may relate to the increased inflammation characteristic of these diseases, but the exact etiology is unknown (8 ).…”
mentioning
confidence: 99%
“…Risk probably remains elevated, although to a much lower degree, during remission. Such risk has been calculated (1.0 per 100 person-years) in only 1 study 4 and was not formally compared to the published data on healthy persons available at the time 5 ; but dissection of data from the other studies of VTE in AAV 1,2,3 and addition of data from new and very large cohorts of healthy persons support the statement that the relative risk of VTE during quiescent AAV is elevated, probably to about the same degree as in rheumatoid arthritis or inflammatory bowel disease 6,7,8 . The increased risk of VTE in AAV, regardless of disease activity, cannot be attributed to the known risk factors for VTE 2,4,9 .…”
mentioning
confidence: 89%
“…It is well established that active antineutrophil cytoplasmic antibody-associated vasculitis (AAV) -granulomatosis with polyangiitis (Wegener's; GPA) or microscopic polyangiitis -is associated with a very high risk of venous thromboembolic events (VTE): about 7 per 100 person-years 1,2,3,4 , compared to 0.15-0.31 in the general population 5,6,7 . Risk probably remains elevated, although to a much lower degree, during remission.…”
mentioning
confidence: 99%